Hubungan Tingkat Kebisingan dengan Gangguan Pendengaran Penduduk di Sekitar Terminal Pakupatan - Linardita Ferial; Laila Fitria; Ririn Arminsih Wulandari (Universitas Faletehan, 2022)
Activities at the bus station may cause environmental pollution, including noise. High noise levels can cause human health problems, especially hearing loss. This study aims to determine the correlation between noise level and hearing loss of the population around Pakupatan Bus Station. This study used an analytical observational approach with a cross sectional design. The survey was conducted in six residences around Pakupatan Bus Station in Serang City, Banten from January to May 2018. The samples of this study were 100 respondents selected by proportional random sampling technique. The noise level of residents around Pakupatan Bus Station reached 81.09 decibels which exceeded the noise quality standard of 55 decibels in 1996 No. 48 of the Ministry of Environment. The confounding variables included age, sex, health history, type of work, smoking, drinking, and length of stay of the respondents. Type of work and length of stay were the confounding variables of the correlation between noise level and hearing loss. The odd ratio of the type of work was 0.267 and the length of stay was 0.365, so it was necessary to apply green lines or to plant trees. The residents who were exposed to noise >70dB had a risk of 4.673 times higher than the noise level 70dB after being controlled by the variable length of stay and variable work.